2017
DOI: 10.5812/jjm.12677
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Composition of the Fermentation Broth of Streptomyces Parvus 33

Abstract: Background: Microorganisms represent a potentially valuable source of biologically significant compounds that should be explored for their potential agrochemical use. Objectives: The compounds ZM-1 and ZM-2 were isolated from the extract of the fermentation broth of Streptomyces parvus 33 by bioassay-guided fractionation. Methods: The compound ZM-1 was isolated in the form of a clear single crystal for the first time, and identified as holomycin via X-ray crystallography. The compound ZM-2 was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Typically, Streptomyces parvus is considered as a potential source of biologically active compounds that has been explored widely for drug development [3]. For example, ZM-1 (identified as holomycin) was isolated from S. parvus 33 and found to have strong antibacterial activity against plant pathogenic fungi [4]. S. parvus NEAE-95 produced an anti-neoplastic agent, L-asparaginase, which was used in acute lymphoblastic leukemia treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Streptomyces parvus is considered as a potential source of biologically active compounds that has been explored widely for drug development [3]. For example, ZM-1 (identified as holomycin) was isolated from S. parvus 33 and found to have strong antibacterial activity against plant pathogenic fungi [4]. S. parvus NEAE-95 produced an anti-neoplastic agent, L-asparaginase, which was used in acute lymphoblastic leukemia treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…This activity was determined to be involved in the inhibition of bacterial RNA polymerase (Oliva et al 2001;Qin et al 2013). Holomycin was first discovered in Streptomyces griseus (Ettlinger et al 1959) and later was reported to be isolated from a number of Streptomyces species (Okamura et al 1977;Kenig and Reading 1979;Ding et al 2017;Wei et al 2017;Zhang et al 2017). The Gram-negative bacteria Photobacterium halotolerans and Yersinia ruckeri were also found to produce holomycin (Wietz et al 2010;Qin et al 2013).…”
Section: Introductionmentioning
confidence: 99%